Measuring perceived challenge in digital games: Development & validation of the challenge originating from recent gameplay interaction scale (CORGIS). Issue 137 (May 2020) - Denisova, Alena; Cairns, Paul; Guckelsberger, Christian; Zendle, David
Highlights: Scale measuring perceived challenge in video games. Four sub-scales (30 items) measuring four types of perceived challenge in video games: cognitive, performative, emotional, and decision-making challenge. Development and validation are carried out over three studies including 1390 players with diverse backgrounds playing video games from a range of genres. The questionnaire is a systematic, extensive, reliable, and valid tool to measure perceived challenge in video games. Abstract: Challenge is a key element of digital games, but a clear conceptualisation and operationalisation of this player experience were long missing. This made it hard for game researchers to measure this experience in different video games across different skill sets and impeded the synthesis of challenge-related games research. To overcome this, we introduce a systematic, extensive, and reliable instrument to evaluate the level of players' perceived challenge in digital games. We conceptualise challenge based on a survey of related literature in games user research, design and AI, as well as interviews with researchers and players. Exploratory factor analysis (N=394) highlights four components of experienced challenge: performative, emotional, cognitive and decision-making challenge. Refinement of the items allowed us to devise the Challenge Originating from Recent Gameplay Interaction Scale (CORGIS), which has been further validated in a study with nearly 1000 players. The questionnaire exhibits good construct validity for use by both game developers and researchers to quantify players' challenge experiences.